PELATIHAN TEKNIK DASAR PENELITIAN ILMIAH BAGI KOMUNITAS PENDIDIKAN: Basic Research Methodology Training for the Educational Community - Akhmad, Nur Amaliah; Nursamsi, Andi; Gustina; Hamsyah, Eka Fitriana (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2025)
Abstract: This community service program was initiated to strengthen the scientificresearch capabilities of the educational community, especially among teachers anduniversity students. The training provided a practical introduction to fundamentalresearch techniques, including problem formulation, data collection, and researchreporting. The program was delivered through four weekly online sessions utilizingZoom and WhatsApp to facilitate interactive and flexible learning—a total of 15participants engaged in theoretical discussions and practical assignments, culminatingin creating mini-research proposals. Evaluation data collected through observation andquestionnaires demonstrated a significant improvement in participants' understandingand confidence in conducting basic research. By emphasizing contextual relevance anddirect application, this initiative successfully enhanced participants' academic writingskills and promoted a research-oriented mindset. The outcomes suggest that short-term,application-based training can be an effective strategy to build research capacity ineducational settings. Keywords: training; research technique; education community   Abstrak: Program pengabdian masyarakat ini diselenggarakan untuk memperkuatkemampuan penelitian ilmiah di kalangan komunitas pendidikan, khususnya guru danmahasiswa. Pelatihan ini bertujuan memberikan pengenalan praktis terhadap teknikdasar penelitian, mencakup rumusan masalah, pengumpulan data, dan penyusunanlaporan penelitian. Kegiatan dilakukan dalam empat sesi daring mingguan melaluiZoom dan WhatsApp guna menciptakan proses pembelajaran yang interaktif danfleksibel. Sebanyak 15 peserta mengikuti sesi teori dan praktik, yang diakhiri denganpenyusunan proposal penelitian mini. Data evaluasi yang diperoleh dari observasi dankuesioner menunjukkan peningkatan signifikan dalam pemahaman dan kepercayaan diripeserta dalam melakukan penelitian dasar. Dengan menekankan konteks aplikatif danrelevansi langsung, kegiatan ini berhasil meningkatkan keterampilan penulisan akademik peserta serta mendorong tumbuhnya budaya riset. Hasil pelatihan menunjukkan bahwa pelatihan jangka pendek berbasis aplikasi dapat menjadi strategi efektif dalam membangun kapasitas riset di lingkungan pendidikan. Kata kunci: pelatihan; teknik penelitian; komunitas pendidikan